Predictors of rebleeding and in-hospital mortality in patients with nonvariceal upper digestive bleeding - Lazăr, Daniela Cornelia (World J Clin Cases, 2019)
BACKGROUND: Nonvariceal upper digestive bleeding (NVUDB) represents a severe emergency condition and is associated with significant morbidity and mortality. Despite a decrease in the incidence due to the widespread use of potent therapy with proton pump inhibitors as well as the implementation of modern endoscopic techniques, the mortality rate associated with NVUDB is still high. AIM: To identify the clinical, biological, and endoscopic parameters associated with a poor outcome in patients with NVUDB to allow the stratification of risk, which will lead to the implementation of the most accurate management. METHODS: We performed a retrospective study including patients who were admitted to the Gastroenterology Department of Clinical Emergency County Hospital Timisoara, Romania, with a diagnosis of NVUDB between 1 January 2008 and 31 December 2016. All the data were collected from the patient’s records, including demographic data, medication history, hemodynamic status, paraclinical tests, and endoscopic features as well as the methods of hemostasis, rate of rebleeding, need for surgery and death; we also assessed the Rockall score of the patients, length of hospitalization and associated comorbidities. All these parameters were evaluated as potential risk factors associated with rebleeding and death in patients with NVUDB. RESULTS: We included a batch of 1581 patients with NVUDB, including 523 (33%) females and 1058 (67%) males with a median age of 66 years. The main cause of NVUDB was peptic ulcer (73% of patients). More than one-third of the patients needed endoscopic treatment. Rebleeding rate was 7.72%; surgery due to failure of endoscopic hemostasis was needed in 3.22% of cases; the in-hospital mortality rate was 8.09%, and the bleeding-episode-related mortality rate was 2.97%. Although our predictive models for rebleeding and death had a low sensitivity, the specificity was very high, suggesting a better discriminative capacity for identifying patients with better outcomes. Our results showed that the Rockall score was associated with both rebleeding and death; comorbidities such as respiratory conditions, liver cirrhosis and sepsis increased significantly the risk of in-hospital mortality (OR of 3.29, 2.91 and 8.03). CONCLUSION: Our study revealed that the Rockall score, need for endoscopic therapy, necessity of transfusion and sepsis were risk factors for rebleeding. Moreover, an increased Rockall score and the presence of comorbidities were predictive factors for in-hospital mortality.